Toward a Moral Grounded Legal Order: India–Indonesia Heritage and the Prophetic Paradigm of Law - Laode Azizul Kadir; Priyanka Kacker (CV. Cognispectra Publishing, 2026)
Purpose of the Study: This study aims to examine the limitations of the positivistic paradigm in understanding Indonesian law and analyse the legal paradigms of prophetic-transcendental. Absorbs as an alternative epistemology that is capable of presenting justice, spirituality, and meaning in more humane laws. Methodology: This research uses a qualitative normative methodology with a philosophical approach to law through conceptual, hermeneutic, and comparative studies, and a positivistic law perspective. Results: The Study finds that the legal paradigm is prophetic, not only critiquing positivism, but also offering a transformative framework that integrates reason, moral values, and spirituality as the foundation for developing a more national, holistic, and civilised law. Applications of This Study: The results of this study can be implemented in reforming the education law, drafting regulations based on value, updating practice responsive ​ to justice, as well as formulating a direction for national political law. Novelty / Originality of This Study: This research focuses on the formulation of prophetic legal paradigms as a legal epistemology, a unifying alternative that combines knowledge, faith, and context, as well as social aspects, while simultaneously reconstructing the ontology, epistemology, and axiology of Indonesian law towards a system that values fairness, humanity, and spirituality. In essence, the prophetic legal paradigm offers Indonesia a transformative path toward a just system, rooted not only in legality but also in morality, human dignity, and spiritual wisdom. By drawing from its own traditions and learning from India's value-based constitutional practices, Indonesia can build a legal order that is fair, humane, and oundly meaningful